Measurement of Λ transverse polarization in e + e − collisions at s $$ \sqrt{s} $$ = 3.68 − 3.71 GeV - The BESIII collaboration; M. Ablikim; M. N. Achasov; P. Adlarson; R. Aliberti; A. Amoroso; M. R. An; Q. An; Y. Bai; O. Bakina; R. Baldini Ferroli; I. Balossino; et al. (Journal of High Energy Physics, 2023)
Abstract With data samples collected with the BESIII detector at seven energy points at s $$ \sqrt{s} $$ = 3.68 − 3.71 GeV, corresponding to an integrated luminosity of 333 pb −1, we present a study of the Λ transverse polarization in the e + e − → Λ Λ ¯ $$ Λ \overline{Λ} $$ reaction. The significance of polarization by combining the seven energy points is found to be 2.6σ including the systematic uncertainty, which implies a non-zero phase between the transition amplitudes of the Λ Λ ¯ $$ Λ \overline{Λ} $$ helicity states. The modulus ratio and the relative phase of EM-psionic form factors combined with all energy points are measured to be R Ψ = 0.71 − 0.10 + 0.10 $$ {0.71}_{-0.10}^{+0.10} $$ ± 0.03 and ∆ΦΨ = 23 − 8.0 + 8.8 $$ {23}_{-8.0}^{+8.8} $$ ± 1.6°, where the first uncertainties are statistical and the second systematic.